2019
DOI: 10.1002/ddr.21605
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy induction in the treatment of Alzheimer's disease

Abstract: A growing body of evidence indicates that autophagy, an intracellular degradation pathway, profoundly affects Alzheimer's disease (AD) pathogenesis. Autophagy mediates the degradation of neurotoxic material and damaged organelles, allowing their clearance by glial and neuronal cells, while impaired autophagy may account for the accumulation of protein aggregates. Accordingly, dysfunctional autophagy is one of AD hallmarks; it occurs early in the disease development, which makes it an attractive therapeutic int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 71 publications
2
17
0
Order By: Relevance
“…e metabolism of Aβ and Tau is strongly associated with autophagy, regulating autophagy is regard as one of the most promising therapeutic strategies [34][35][36][37]. Under normal circumstances, activation or a certain degree of enhancement of autophagy can significantly eliminate Aβ deposition, promote Tau clearance, and alleviate neurodegeneration [34,38,39]. Some researchers added Aβ 1-42 to SH-SY5Y cells and found that it can cause a certain cytotoxic effect on the cells.…”
Section: Discussionmentioning
confidence: 99%
“…e metabolism of Aβ and Tau is strongly associated with autophagy, regulating autophagy is regard as one of the most promising therapeutic strategies [34][35][36][37]. Under normal circumstances, activation or a certain degree of enhancement of autophagy can significantly eliminate Aβ deposition, promote Tau clearance, and alleviate neurodegeneration [34,38,39]. Some researchers added Aβ 1-42 to SH-SY5Y cells and found that it can cause a certain cytotoxic effect on the cells.…”
Section: Discussionmentioning
confidence: 99%
“…mTORC1 signaling downregulates the activity of the ULK1 complex, thus repressing autophagy induction. mTORC1 signaling is further regulated by nutrient-sensing kinases such as the AMPK and Akt pathways [55]. Additionally, PI3K acts as a major upstream modulator of mTOR and can further regulate autophagy via different stimuli such as growth factors or insulin [56].…”
Section: Elegans: a Model For Researchmentioning
confidence: 99%
“…Autophagy plays a widespread role in both physiological and multiple pathological conditions, including cancer and neuronal disorders [ 17 ], and is extensively involved in the pathogenesis of AD [ 18 ]. Autophagy, a self-digesting mechanism, is an intracellular cleansing process characterized by the engulfment of malformed proteins and damaged cellular organelles by membrane-bound vesicles known as autophagosomes [ 17 ].…”
Section: Introductionmentioning
confidence: 99%